2020
DOI: 10.31024/ajpp.2020.6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of different polyphenols in the treatment of cancer disease

Abstract: Cancer is basically uncontrolled proliferation of cells with altered genetic constituents accompanied by migration from one part of the body to another due to loss of their binding ability and interconnectivity. It has already become a global health problem and the occurrence is increasing day by day with urbanisation and changes in dietary patterns constituting the main reason of its occurrence in addition to genetic causes. The aim of this review is to highlight the pharmacological activity of polyphenols ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 100 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Phenols regulate enzyme activity and cell receptors. Studies have shown the protective function of polyphenols such as quercitrin, quercetin, catechin, epicatechin, kaempferol and sinapinic acid in the management of cancer cardiovascular and neurodegenerative conditions [31][32][33][34][35][36]. These and other phytochemicals were quantified via HPLC in the leaf extract of C. olitorius.…”
Section: Proximate Composition Mineral Contents Phytochemical Screeni...mentioning
confidence: 99%
“…Phenols regulate enzyme activity and cell receptors. Studies have shown the protective function of polyphenols such as quercitrin, quercetin, catechin, epicatechin, kaempferol and sinapinic acid in the management of cancer cardiovascular and neurodegenerative conditions [31][32][33][34][35][36]. These and other phytochemicals were quantified via HPLC in the leaf extract of C. olitorius.…”
Section: Proximate Composition Mineral Contents Phytochemical Screeni...mentioning
confidence: 99%